The Psychology of Pro-Environmental Communication - Klöckner, Christian A. author. aut Link
X, 271 p.
Keywords: The environment is part of everyone's life but there are difficulties in communicating complex environmental problems, such as climate change, to a lay audience. In this book Klöckner defines environmental communication, providing a comprehensive and up-to-date analysis of the issues involved in encouraging pro-environmental behaviour.